PTU-317 Is it worth offering ct colonography (ctc) in patients considered unfit for colonoscopy in a nurse (ssp) pre-assessment clinic within the bowel cancer screening programme?. (22nd June 2015) - Taggart, N; Hymer, W; Mbuyongha, M; Mark, H; Fitzgerald, G; Sarkar, S
Abstract : Introduction: Whilst colonoscopy is the only test offered within the BCSP after a positive faecal occult blood (FOB) result, there is often a dilemma whether to offer an alternative test in borderline cases especially now the CTC can be performed without administering full bowel prep. The aim of this study was to review CTC offered as an alternative test following SSP clinic within the Liverpool and Wirral BCSP programme to determine the outcome of patients deemed unfit for colonoscopy. Method: Datasets and notes of all patients that were deemed as high risk for colonoscopy following SSP assessment that underwent a CTC on the advice of a BCSP colonoscopist were audited between May 2014 and Jan 2015. Results: Of the 481 patients assessed, 13 underwent CTC (2.7%). The reasons for requesting a CTC were listed as: anticoagulant/anti-platelet therapy in conjunction with permanent pace maker (PPM), implantable cardioverter defibrillator (ICD), CA stents, severe valvular heart disease (n = 6), unstable angina and chronic obstructive pulmonary disease COPD (n = 5), ulcer on abdominal aorta (n = 1) and previous failed colonoscopy (n = 1). MH comments – I would use words rather than abbreviations for PPM, ICD, CA and COPD. The results of the CTC were; normal in 5, minor extra-colonic findings in 3, polyps in 4 and likely colorectal malignancy in 1, meaning that 38% of patients that underwent a CTC had a significant colonic abnormality. Eight patients (62%) were discharged back to the screening programme. The patient with likely colorectal malignancy was referred to MDT and 4 with significant polyps underwent further investigation. Two had flexible sigmoidoscopy with just enema prep, 1 with polypectomy and the other had a polyloop applied to the polyp stalk without polypectomy whilst they continued on Ticagrelor. Another underwent a full colonoscopy with polypectomy. The final patient with a possible small polyp opted for a repeat CTC 6 months after MDT and patient discussion. There were no complications following the 3 endoscopic procedures. Conclusion: Only a very small percentage went onto have a CTC following SSP clinic. The yield of the CTC was significant. A negative result offered reassurance with a Faecal Occult Blood Test in 2 years. Meanwhile, a positive result tipped the risk to benefit ratio to an ultimately good outcome in these patients as less extensive procedures such as a sigmoidoscopy without oral bowel prep, alternatives to polypectomy or a follow up CTC could be offered. Disclosure of interest: None Declared.